Avaliação dos investimentos dos fundos de previdência complementar no Brasil - Bicalho, Filipe Carneiro (2018)
Nowadays, in the midst of increased life expectancy, which means a higher proportion of elderly to young, the situation of Brazil’s Public Pension system has turned out to be the focus of many questionings, mostly about its sustainability. Being aware of the fragilities of the social security system and a clear necessity of a reform, investors are looking more and more to alternative ways to guarantee some income after they retire. One of the most obvious investments are the pension funds, which have been on the spot ever since Brazil has been in this scenario of uncertainties. Considering this greater visibility that this scenario has brought to pension funds, this work intends to make an evaluation of the performance of them, during the years of 2010 to 2015. Having this in mind, this paper will look into the return of the investments of pensions funds during those years mentioned, searching for explanations to have a better understanding of the causes of the performance of these funds. This analysis will be done by a dynamic panel model, which will test how economic indexes can affect the investments of these funds.